Pembuatan Eco Paving Berbahan Campuran Limbah Plastik Dalam Upaya Peningkatan Infrastruktur Jalan Lingkungan dan Pendapatan Masyarakat di Desa Grogol, Kecamatan Giri - Naris Wari, Wahyu; Dwi Pranowo, Dadang; Pradita, Rahayu; Olivia Hutasoit, Eva (Politeknik Negeri Jember, 2024)
The problem of road infrastructure and plastic waste management faced by Grogol Village does require innovative solutions such as training in the use of plastic waste to make paving blocks. By using plastic waste as a mixture in paving blocks, the village can reduce plastic waste and improve the quality of roads that are the main access for residents and tourists. The steps taken in making paving blocks through the stages of waste processing, preparation of tools and materials, to compressive strength testing after 28 days of treatment. . Test objects by mixing cement, water, sand and plastic shreds. The ratio used for the cement mixture with sand is 1: 2.75, with a paving size of 10x 20 x 6 cm in 1 variation of test objects. The test objects consist of 3 variations, namely normal paving, normal paving added with 0.25% and 0.50% plastic shreds. After the test objects are molded, they are then treated for 28 days to carry out compressive strength testing at the age of 28 days. Thus, this training not only provides environmental benefits through plastic waste management, but also improves the local economy and supports the development of more sustainable village infrastructure